A continued racial character of some of the Gereformeerde Kerke in South Africa: Strategic moves evading reconciliation and unity of churches in post-apartheid South Africa - Baloyi, Elijah ca. 20./21. Jh. (HTS teologiese studies, 2018)
The quest for liberation of all South Africans from past racial divides since the inception of democratic government has been prioritised for more than 24 years now. Although this is an ongoing process and some achievements have been made to this end, it is yet evident that the impact of racism and apartheid still influence many lives both in and outside the churches. The Gereformeerde Kerke in South Africa (GKSA) is amongst the churches that officially removed the barriers of apartheid to have one united church. The relevant question would be to ask if relatively good progress had been made towards uniting these churches. This article intends to unveil evidence in the form of case studies that reconciliation and unity are still a journey which the members of the mentioned church should embark on. There are members of some congregations under this church who are still held within the culture of separation and hence they make it difficult to unify the church. The foundation for reconciliation had been laid down, but the challenge is now to build unity upon it. Despite some racial signs still visible in some churches, this article concerns itself in looking a place where unity, peace and reconciliation are expected to be at the top of the agenda. The article attempts to propose some strategies towards unity within the GKSA. Practical case studies will be consulted to indicate the existence of the challenge of racism in the GKSA, despite efforts to eradicate it from government and other stakeholders concerned.